2016
DOI: 10.3390/ijerph13111168
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Parental Risk Factors for Speech Disability Associated with Cleft Palate in Chinese Children—A National Survey

Abstract: Abstract:Although the prevalence of oral clefts in China is among the highest worldwide, little is known about the prevalence of speech disability associated with cleft palate in Chinese children. The data for this study were collected from the Second China National Sample Survey on Disability, and identification of speech disability associated with cleft palate was based on consensus manuals. Logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs). A weighted number of 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
(52 reference statements)
3
3
0
Order By: Relevance
“…Univariate analysis demonstrated that the MSD phenotype was associated with a lower educational level and a greater amount of manual labor, and a monolingual speaking background. These findings were partially in accordance with those of similar studies that focused mainly on the demographic characteristics and relevant evaluations in other types of SD [2225]. Moreover, multivariate logistic regression analysis revealed a lower educational level as an independent risk factor for PD-associated MSD.…”
Section: Discussionsupporting
confidence: 91%
“…Univariate analysis demonstrated that the MSD phenotype was associated with a lower educational level and a greater amount of manual labor, and a monolingual speaking background. These findings were partially in accordance with those of similar studies that focused mainly on the demographic characteristics and relevant evaluations in other types of SD [2225]. Moreover, multivariate logistic regression analysis revealed a lower educational level as an independent risk factor for PD-associated MSD.…”
Section: Discussionsupporting
confidence: 91%
“…Univariate analysis demonstrated that the MSD phenotype was associated with a lower educational level, a greater amount of manual labor, and a monolingual speaking background. These findings were partially in accordance with those of similar studies that focused mainly on the demographic characteristics and relevant evaluations in other types of SD [22][23][24][25]. Moreover, multivariate logistic regression analysis revealed a lower educational level as an independent risk factor for PD-associated MSD.…”
Section: Discussionsupporting
confidence: 91%
“…Univariate analysis demonstrated that the MSD phenotype was associated with a lower educational level and a greater amount of manual labor, and a monolingual speaking background. These findings were partially in accordance with those of similar studies that focused mainly on the demographic characteristics and relevant evaluations in other types of SD [22][23][24][25]. Moreover, multivariate logistic regression analysis revealed a lower educational level as an independent risk factor for PD-associated MSD.…”
Section: Discussionsupporting
confidence: 91%